2004
DOI: 10.1144/gsl.sp.2004.221.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Foreland basin evolution around the western Alpine Arc

Abstract: The arcuate form of the external western Alps was generated during Tertiary NW-directed collision between the Apulian indentor and the southward-subducting European passive margin. The evolution of peripheral syn-collisional depocentres around this arcuate orogen (in France and Switzerland) is reconstructed using a compilation of stratigraphic and tectonic data. This reveals fundamental changes in the flexural behaviour of the European lithosphere during collision. During early collision (Eocene), an increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 75 publications
1
58
0
Order By: Relevance
“…Samples were collected from Oligo-Miocene clastic units of the Alpine pro-foreland basin (Ford and Lickorish, 2004). The sub-300 μm non-magnetic heavy mineral fraction was extracted from rock samples via standard crushing, sieving, and magnetic and density separation techniques.…”
Section: European Alps Samplesmentioning
confidence: 99%
“…Samples were collected from Oligo-Miocene clastic units of the Alpine pro-foreland basin (Ford and Lickorish, 2004). The sub-300 μm non-magnetic heavy mineral fraction was extracted from rock samples via standard crushing, sieving, and magnetic and density separation techniques.…”
Section: European Alps Samplesmentioning
confidence: 99%
“…He showed that Alpine stresses were only transmitted into the foreland when they could not be accommodated within the orogen or flexural foreland basin. Ford and Lickorish [2004] provided evidence for continued flexural subsidence from Oligocene to late Miocene in the North Alpine Foreland basin. Subsequent alpine deformation and uplift is seen in the Paris Basin, the Rhine Graben, the Lulworth folds of southern Britain and Late Tertiary inversion in the North Sea.…”
Section: Mechanismsmentioning
confidence: 94%
“…While tensional subsidence of the northern parts of the upper Rhine Graben continued without interruptions to the present, its southern parts were uplifted by about 1,500 m during mid-Burdigalian time (18 Ma) in conjunction with the development of the Vosges-Black Forest Arch, involving lithosphere-scale folding (Ziegler et al 2002;Dèzes et al 2004;Ziegler and Dèzes 2007). Ford and Lickorish (2004) and Bourgeois et al (2007) proposed that this topographic high represented the Fig. 4 a Chronology of (i) sediment accumulation and erosion in the Molasse Basin, (ii) drainage direction in the foreland, and (iii) folding of the Jura fold-and-thrust belt.…”
Section: The Central European Rifts: Upper Rhine and Bresse Grabensmentioning
confidence: 99%